Morphophysiological indices of internal organs of the dice snake Natrix tessellata (Reptilia, Colubridae) of the Dnieper river in the Steppe - Yermolenko, S.V.; Gagut, A.M.; Gasso, V.Ya. (Збірник праць Зоологічного музею, 2016)
We studied morphophysiological indices of organs of the dice snakes, Natrix tessellata (Laurenti, 1768), from three populations in the Steppe Zone of Ukraine along the Dnieper River. The specimens were collected in 2013–2016 in three areas: Prydniprovska Thermal Power-Station (Dnipro City), the National Nature Park “Velykyi Luh”, Zaporizhia region, and Majorova Balka (the ravine closed to Majorka village, Dnipro district, Dnipropetrovska region). Studied biotopes differ in some abiotic parameters and the level of anthropogenic load. Significant differences in kidneys and liver indices between sexes were noted. The relative mass of lung and heart diverges between animals from different studied sites.